MENGKRITISI PERLINDUNGAN KORBAN TINDAK PIDANA MALPRAKTIK MEDIS: PARADIGMA CRITICAL VICTIMOLOGY - Suindrayani, Ni Putu Tya (Jurnal Hukum Statuta, 2025)
Abstract This study aims to determine the ius constitutum for the protection of medical malpractice crimes victim in Indonesia, as well as to find out the critical victimology view in examining the protection of medical malpractice crimes victim in Indonesia. This research is an empirical legal research by analyzing the results of interviews and reviewing them with a critical victimology approach. The conclusion of this study is the ius constitutum for the protection of medical malpractice crimes victim in Indonesia still refers to the Witness and Victim Protection Law, the Medical Practice Law, the Health Law and the Criminal Code and the view that the imposition of criminal sanctions for medical malpractice perpetrators is considered a form of providing legal protection against victims, and another form of fulfilling the rights of victims is to refer to the provision of compensation. Therefore, there are imperfections in the application of victimology theory, especially the critical victimology approach in the provision and enforcement of legal protection for medical malpractice crimes victim in Indonesia. Keywords: Critical Victimology; Malpractice; Victim Protection